Intention to be Bound when Forming Contracts by Automated Means - Drazdauskas, Stasys (Teisė, 2024)
The progress of automation is bringing back doubts in legal research about whether a party should be bound by the steps taken through automated systems used in contract formation. In response to these doubts, the article presents a critique of the so-called ‘separation’ theories, based on the arguments of the asynchrony of the will of the parties, objectivity, and the computer as a tool. It also aims to determine whether international soft law initiatives, as well as national legislation, are developing a universal and unified approach to the impact of automated systems on the conclusion of contracts. The UNCITRAL Commission, the European Law Institute, as well as legislators in both common and civil law jurisdictions, consistently reinforce the principle that contracts concluded by automated means must be recognized as binding, and legal consequences must be attributed to parties using automated systems. In the cases examined from the court practice related to automatically concluded contracts, the problem of assigning legal effects to the party using an automated system does not arise in principle.